Exploration of the Optimal Desmopressin Treatment in Children With Monosymptomatic Nocturnal Enuresis: Evidence From a Chinese Cohort - Liu, Jiaojiao; Ni, Jiajia; Miao, Qianfan; Wang, Chunyan; Lin, Fang; Cao, Qi; Guo, Wei; Yang, Xue; Ji, Xiaolu; Zhai, Yihui; Bi, Yunli; Shen, Qian; et al. (Frontiers in Pediatrics, 2021)
Objectives: Nocturnal enuresis (NE) is a common paediatric condition, and desmopressin (dDAVP) is a first-line therapy for NE. The standard initial dosage of dDAVP is 0.2 mg/day, and the majority of guidelines recommend that the dose should be increased at 0.2 mg increments until dryness is achieved or to the maximal recommended dose. However, previous evidence showed that this strategy seems insufficient to further improve efficacy and results in unnecessarily high doses for some patients. Our study aimed to assess the efficacy of our modified dDAVP treatment regimen in children with MNE in China and evaluate predictive factors associated with the dDAVP response. Methods: All MNE patients at the Department of Nephrology at Children’s Hospital of Fudan University from January to December 2019 were prospectively and consecutively enrolled. dDAVP treatment consisted of a dose titration period and a 3-month maintenance period. Efficacy of dDAVP was assessed according to the latest International Children’s Continence Society criteria at the end of the study. Predictive factors were evaluated by logistic regression analysis. Results Overall, 322 MNE patients were enrolled in our study, and 225 (69.9%) completed the study. The intention to treat analysis showed the overall dDAVP response rate was 69.9%, among them 32.3% were CRs, 37.6% were PRs. At the end of the study, 194/225 (86.2%) patients received final doses of 0.2 mg, 24/225 (10.7%) patients received final doses of 0.3 mg, and 7/225 (3.1%) patients received final doses of 0.4 mg. Multivariate analysis showed that patients requiring lower doses to achieve responses were significantly more likely to experience CRs during maintenance period (odds ratio (OR)=9.683; 95% confidence interval (CI), 2.770-33.846). Conclusions Our results indicate that the DDAVP treatment regimen provides a comparable efficacy to the international conventional treatment regimen with a lower overall dose. Low-dose responders were likely to achieve CRs without increasing the dose, and in these cases, the maximum dose might not necessary.